Investigating physical fitness of students: A multi-dimensional analysis of health-related fitness test metrics - Gula, Louie P.; Sumayang, Kevin R.; Sapan, Mary Jean M.; Millan, Ma. Shella R.; Hermosilla, Leo A.; Austero, Edgar Alabado (Journal of Physical Education (Maringá), 2025)
This study aimed to examine the current state of health-related fitness assessments in physical education programs. This study was undertaken with the overarching objective of conducting a comprehensive analysis of the present landscape pertaining to health-related fitness assessments within physical education programs. This study made use of the Quasi-experimental research design, like experimental designs, aim to test causal hypotheses. Both randomized controlled trials (RCTs) and quasi-experimental designs evaluate programs or policies as “interventions,” assessing how well the treatment—comprising the elements of the program or policy—achieves its goals based on a set of predetermined indicators. The presented data explores the correlations between various post-exercise physiological and performance metrics among a sample of 50 participants. Significant correlations at the 0.05 and 0.01 levels (2-tailed) are highlighted. Age shows a notable positive correlation with the first attempt performance (r = 0.336, p < 0.05) and second attempt performance (r = 0.296, p < 0.05), indicating older participants tend to perform better on these attempts. The data underscore the complex interrelationships between demographic factors, body composition, physiological responses, and performance assessments. Male shows demonstrated greater height output in comparison to females and average height was found to correlate negatively with BMI. The relationship between muscular strength and endurance is strong. Although it shows inconsistency in HR measurement. The associations between pre-exercise heart rate and post-exercise heart rate, and the significant correlations of muscular strength, endurance are good examples to show the links between the different physical performance measures.